Managing Disaster-Related Health Risk: A Process for Prevention. Issue 3 (1st June 2018) - Keim, Mark
Abstract: In 1994, the first World Conference on Natural Disaster Reduction held in Yokohama, Japan affirmed that "Disaster prevention, mitigation, and preparedness are better than disaster response in achieving the goals and objectives of the decade. Disaster response alone is not sufficient, as it yields only temporary results in a very high cost." Since then, disaster risk reduction has become the mainstay for international development related to disasters. According to the National Research Council (Washington, DC USA), "Disaster research, which has focused historically on emergency response and recovery, is incomplete without the simultaneous study of the societal hazards and risks associated with disasters, which includes data on the vulnerability of people living in hazard prone areas." Despite over 25 years of global policy development, the National Academies of Sciences, Engineering, and Medicine (Washington, DC USA) recently noted that, "while some disaster management and public health preparedness programming may be viewed as tangentially related, a multi-sectoral and inter-disciplinary national platform for coordination and policy guidance on involving disaster risk reduction in the United States does not exist." Today, one of the world's "seven targets in seven years" as agreed upon in the Sendai Framework for Disaster Risk Reduction is to substantially reduce global mortality by 2030. Significant reductions in health risk (including mortality) have historically required a comprehensive approach for disease management that includes both a preventive and a curative approach. Disaster risk management has arisen as a primary means for the world's populations to address disaster losses, including those related to health. Prevention has been proven as an effective approach for managing health risk. This report describes the role of disease prevention in managing health risk due to disasters. M Keim .Managing disaster-related health risk: a process for prevention .Prehosp Disaster Med .2018 ;33 (3 ):326 -334 .